Answer:
Y = 2/3x-8/3
Step-by-step explanation:
y − 4 = 2/3 ( x − 3)
y − 4 = 2/3x -2
y = 2/3x +2
~~~~~~~~~~~~~~~~~
-2 = 2/3(1) + b
b = -2 2/3 = -8/3
f(x) = y, when the graph touches the y-axis, x = 0.
-2+3x=2x+6+x
-2+3x= 3x+6
-3x = -3x
-2=6
No solution! -2 doesn’t not equal 6
Steps
1. Combine like terms( example combine like terms on the right side of the equation)
2. Subtract or add variable from one side
3. You get the answer
Sub
(x,y)
(-3,y)
x=-3
y=y
y=3-(-3)
y=3+3
y=6
y=6 which is mysteriously not listed